Tracking the Sustainable Development Goals: Emerging Measurement Challenges and Further Reflections - Hai-Anh H. Dang; Haishan Fu; Umar Serajuddin (Global Labor Organization (GLO), 2019)
The Sustainable Development Goals (SDGs) recently adopted by the United Nations represent an important step to identify shared global goals for development over the next two decades. Yet, the stated goals are not as straightforward and easy to interpret as they appear on the surface. Review of the SDG indicators suggests that some further refinements can be made to their wordings, and their underlying objectives can be further clarified. We bring attention to potential pitfalls with interpretation, where different evaluation methods can lead to different conclusions about country performance. Review of the United Nations' SDG database highlights the overwhelming challenge with missing data: data are available for just over half of all indicators and for just 19 percent of what is needed to comprehensively track progress across countries and over time. We offer further reflections and propose some simple but cost-effective solutions to these challenges.
Keywords: F00; I3; O1; 330; SDGs; monitoring; data challenges; survey data; international organization